2019
DOI: 10.1093/ijnp/pyz046
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Adverse Reactions During Antipsychotic Treatment: Results of AMSP, A Drug Surveillance Program Between 1993 and 2013

Abstract: Background Cardiovascular diseases are still the leading cause of global mortality. Some antipsychotic agents can show severe cardiovascular side effects and are also associated with metabolic syndrome. Methods This observational study was based on data of AMSP (Arzneimittelsicherheit in der Psychiatrie), a multicenter drug surveillance program in Austria, Germany and Switzerland, that recorded severe drug reactions in psychi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 25 publications
3
16
0
3
Order By: Relevance
“… 54 Analysis of a database encompassing Austria, Germany, and Switzerland reported a QTc prolongation frequency of 0.006% among patients treated with clozapine or quetiapine and 0% with aripiprazole, olanzapine, and risperidone. 55 …”
Section: Antipsychoticsmentioning
confidence: 99%
See 2 more Smart Citations
“… 54 Analysis of a database encompassing Austria, Germany, and Switzerland reported a QTc prolongation frequency of 0.006% among patients treated with clozapine or quetiapine and 0% with aripiprazole, olanzapine, and risperidone. 55 …”
Section: Antipsychoticsmentioning
confidence: 99%
“…Aripiprazole was mentioned in 6 systematic reviews and meta-analyses, 30 , 31 , 56–59 13 prospective or observational studies, 33 , 47 , 55 , 60–69 and 4 case reports. 70–73 The literature consistently showed that aripiprazole is associated with small reductions in QTc interval.…”
Section: Antipsychoticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ap ra ðo mi pa vieniai ðios vais tø gru pës su kel ti kli ni ki niai at ve jai þur na luo se ir FDA ða lu ti niø po vei kiø re gist ro duo me nø ba zë je [32,33]. Ty ri muo se su svei kais sa va no riais di dþiau sià QTc pail gë ji mà ið ati pi niø neu ro lep ti kø su ke lia zip ra zi do nas, ly gi nant já su olan za pi nu, ris pe ri do nu, kve tia pi nu, ta èiau jo arit mo ge ni nis po vei kis në ra di de lis [30,34]. Ne pai sant keliø su di de lë mis olan za pi no do zë mis sie ja mø ap ra ðy tø QTc pail gë ji mo at ve jø [35], au to riai ðá vais tà sie ja su ne di de le arit mi jø ri zi ka [36].…”
Section: Elektrofiziologiniai Pokyèiai Ir Aritmijosunclassified
“…In particular, schizophrenia, a complex and heterogeneous mental disorder, which is often difficult to treat, is associated with a higher risk of polypharmacotherapy and trialand-error treatment choices [5,[14][15][16]. Antipsychotic drugs, used to treat psychosis and thus schizophrenia (among other mental disorders), are further reported to show a high interindividual variability in drug serum concentration [17][18][19] and cause a vast array of serious ADRs (such as agranulocytosis, extrapyramidal motor symptoms, or malignant neuroleptic syndrome), justifying consequent drug monitoring [20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%